Chemical composition and modulation of bacterial drug resistance of the essential oil from leaves of Croton grewioides. (October 2017) - de Medeiros, Vivianne Marcelino; do Nascimento, Yuri Mangueira; Souto, Augusto Lopes; Madeiro, Sara Alves Lucena; Costa, Vicente Carlos de Oliveira; Silva, Suellen Maria P.M.; Falcão Silva, Vivyanne dos Santos; Agra, Maria de Fátima; de Siqueira-Júnior, José Pinto; Tavares, Josean Fechine
Abstract: The essential oil from leaves of Croton grewioides Baill was obtained by hydrodistillation using Clevenger apparatus, and its chemical composition was analyzed by GC-MS, where 18 compounds were identified, mostly as monoterpenes (55.56%) and sesquiterpenes (44.44%), in which the major constituent was the α-pinene (47.43%). The essential oil of Croton grewioides (EO Cg ) and its major compound (α-pinene) were evaluated as modulators of antibiotic resistance in strain SA-1199B and IS-58 of Staphylococcus aureus that overexpresses efflux protein. The minimum inhibitory concentrations (MICs) of the antibiotics were determined by the microdilution assay in the absence and in the presence of sub-inhibitory concentration of EOCg and α-pinene. Although the EO Cg and α-pinene did not indicate relevant antibacterial activity in vitro, they acted as antibiotic resistance modulators, i.e., EOCg in combination with norfloxacin, reducted its MIC, by 64× whereas in combination with tetracycline it was observed a reduction of 4×. Additionally, it was observed a MIC reduction of tetracycline by 32×, when combined with α-pinene. The results suggest that EO Cg and α-pinene modulate or even reverse bacterial resistance as a putative efflux pump inhibitor. Highlights: The essential oil and α-pinene had a synergistic effect when associated with the antibiotics. Essential oil exhibited the best result. Reducing the MIC of norfloxacine and tetracicline, essential oil, α-pinene are consider as a putative efflux pump inhibitor.